2018
DOI: 10.1007/s00109-018-1715-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular signatures involved in radiation-induced lung fibrosis

Abstract: In radiotherapy, radiation (IR)-induced lung fibrosis has severe and dose-limiting side effects. To elucidate the molecular effects of IR fibrosis, we examined the fibrosis process in irradiated mouse lung tissues. High focal IR (90 Gy) was exposed to a 3-mm volume of the left lung in C57BL6 mice. In the diffused irradiation, 20 Gy dose delivered with a 7-mm collimator almost covered the entire left lung. Histological examination for lung tissues of both irradiated and neighboring regions was done for 4 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…A recent study reported that FGL1 as a molecular candidate for radiation-induced lung fibrosis suggesting the involvement of radiation epithelial to mesenchymal transition using L132 human pulmonary epithelial cells [28]. Consistent with this previous report, irradiated HH showed upregulation of fibrotic/mesenchymal markers such as α-SMA and FSP-1 when FGL1 is elevated in Figure 3.…”
Section: Discussionsupporting
confidence: 85%
“…A recent study reported that FGL1 as a molecular candidate for radiation-induced lung fibrosis suggesting the involvement of radiation epithelial to mesenchymal transition using L132 human pulmonary epithelial cells [28]. Consistent with this previous report, irradiated HH showed upregulation of fibrotic/mesenchymal markers such as α-SMA and FSP-1 when FGL1 is elevated in Figure 3.…”
Section: Discussionsupporting
confidence: 85%
“…These NPs further reduced the expression of GTSE1, whose protein product binds p53 and thus blocks apoptosis. Its expression was observed in radiation-induced lung fibrosis [36]. The exposure to 24h50 nCD was associated with the downregulation of GTSE1 as well as CDCA3 and expression.…”
Section: Discussionmentioning
confidence: 90%
“…GTSE1, a microtubule-localized protein, was reported to overexpress in many kinds of human cancer and negatively regulate the functions of p53 [ 19 , 20 ]. It has been reported that the high GTSE1 expression contributes to the malignant behavior of human cancer [ 10 , 21 ]. In neuroendocrine tumors, overexpression of GTSE1 can augment aggressive phenotypes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%